Analisis Tata Kelola Teknologi Informasi Menggunakan Framework COBIT 5 - Yohanes Agung Apriyanto; Arif Aliyanto (Jurnal Ilmiah Matrik, 2025)
The utilization of information technology (IT) in modern business requires the implementation of effective governance to ensure alignment between IT systems and the organization’s strategic objectives. This study aims to analyze the IT governance at PT. Berlian Maju Motor using the COBIT 5 framework, focusing on three core domains: DSS02 (Manage Service Requests and Incidents), DSS03 (Manage Problems), and MEA01 (Monitor, Evaluate and Assess Performance and Conformance). The research employs a descriptive quantitative approach with data collected through observation, interviews, and questionnaires, and analyzed using the Process Assessment Model (PAM). The analysis results show that the current process capability levels for DSS02 and DSS03 are at Level 3 (Established Process), while MEA01 is at Level 2 (Managed Process). Several gaps were identified between the current conditions and the ideal capability levels based on COBIT 5 standards, particularly in aspects such as documentation, incident response, and IT service performance monitoring. Based on these findings, improvement recommendations are proposed, focusing on strengthening service procedures, enhancing documentation, and developing a sustainable IT performance evaluation system.